PENGARUH USIA, KEINGINAN SOSIAL, KECUKUPAN ANGGARAN, DAN PARTISIPASI PENGANGGARAN TERHADAP KINERJA MANAJER DI INDONESIA - R.A. Supriyono (Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
This study investigates the influence of age to manager performance in Indonesia. In the theoretical model, age affects totally to manager performance and this affects can directly or indirectly via three intervening variable: social desirability, budget adequacy, and budgeting participation. To test the relationship, a survey questionnaire was administered to managers of public corporation in Jakarta Stocks Exchange (JSX). Results of regression and path analysis support the hypothesized relationship